2015
DOI: 10.4161/15384101.2014.987621
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 controls IL-2 gene expression via repression of the mSin3a-HDAC complex

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a unique member of a family of serine/threonine cyclin-dependent protein kinases. We previously demonstrated disruption of Cdk5 gene expression in mice impairs T-cell function and ameliorates T-cell-mediated neuroinflammation. Here, we show Cdk5 modulates gene expression during T-cell activation by impairing the repression of gene transcription by histone deacetylase 1 (HDAC1) through specific phosphorylation of the mSin3a protein at serine residue 861. Disruption of Cdk5 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…In T cells, DNA binding assays revealed phosphorylation of Stat3 at S727 is essential for Stat3 binding to the enhancer region II of the Foxp3 gene, and is thereby critical to the repression of Foxp3 expression in T cells exposed to cytokines like IL-6 and IL-27. Thus, our data not only reinforce the role of Cdk5 as an important post-translational modulator of transcription factor activity (Dhavan and Tsai 2001, Lin, Chen et al 2007, Courapied, Sellier et al 2010, Kazmierczak, Czapski et al 2011, Lam, Pareek et al 2015), but also demonstrate the importance of this function in controlling T cell fate. In summary, the observations presented here reveal a novel role of Cdk5 in controlling Foxp3 gene expression and suggest that targeting Cdk5 activity may overcome the ability of inflammatory cytokines to repress TGF-β-induced Foxp3 expression.…”
Section: Discussionsupporting
confidence: 76%
“…In T cells, DNA binding assays revealed phosphorylation of Stat3 at S727 is essential for Stat3 binding to the enhancer region II of the Foxp3 gene, and is thereby critical to the repression of Foxp3 expression in T cells exposed to cytokines like IL-6 and IL-27. Thus, our data not only reinforce the role of Cdk5 as an important post-translational modulator of transcription factor activity (Dhavan and Tsai 2001, Lin, Chen et al 2007, Courapied, Sellier et al 2010, Kazmierczak, Czapski et al 2011, Lam, Pareek et al 2015), but also demonstrate the importance of this function in controlling T cell fate. In summary, the observations presented here reveal a novel role of Cdk5 in controlling Foxp3 gene expression and suggest that targeting Cdk5 activity may overcome the ability of inflammatory cytokines to repress TGF-β-induced Foxp3 expression.…”
Section: Discussionsupporting
confidence: 76%
“…IL-2 is a cytokine signaling molecule in the immune system where it regulates the activities of white blood cells (e.g. lymphocytes) that are responsible for the immunity [ 45 ]. Our results showed that the polysaccharides from Amauroderma rude may function similarly to those from Ganoderma lucidum , by producing these cytokines with potent effects on immunity and anticancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of total cellular lysates and nuclear and cytoplasmic fractions for Western blotting was performed as previously described 81 , 82 . Nuclear-cytoplasmic fractions were separated using NE-PER nuclear and cytoplasmic extraction reagents (Thermo Fischer Scientific Inc.), containing a protease and phosphatase inhibitor (Roche Inc.).…”
Section: Methodsmentioning
confidence: 99%